Malang City Urban Community’s Perception towards Religion and Islamic Education - Mohammad Kamaludin (Universitas Muhammadiyah Malang, 2021)
Malang is known as a city of education, industry, and tourism. With these three names and with the various problems that exist in it, Malang is certain to experience changes in its social relations quickly. Starting from the emergence of the assumption that there has been a change in urban society, especially the view of religion, this study focuses on two aspects, namely the perception of the people of Malang towards religion and how Islamic education affects their daily religious attitudes. The results of observations made by researchers show that the level of education of the urban community is very heterogeneous. However, they were at a fairly high level of ability. This is reflected in several answers to interviews asked by the researcher. None of them did not understand certain terms related to religious education and its elements, such as improving the quality of life, religious phenomena, and others. Therefore, this finding is very different from the previous assumption which states that Malang residents will leave their religion due to various external influences caused by the increasing arrival of urban communities, industry, and tourism.